THE EFFECT OF LIQUIDITY AND LEVERAGE ON TAX AGGRESSIVITY IN FOOD AND BEVERAGE SECTOR COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE 2017-2019 - Icsan Pratama Panjaitan; Marthinus Ismail (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
The effect of liquidity and leverage on tax aggressiveness in food and beverage sector companies listed on the Indonesian stock exchange in 2017-2019. This study aims to determine how liquidity and leverage affect tax aggressiveness. The research sample consisted of 22 from 34 companies and thus there were 66 samples. The research data is a secondary report in the form of financial statements of manufacturing companies listed on the IDX. Data is downloaded via www.idx.co.id. The method used in this research is descriptive statistics, correlation coefficient, determination coefficient, significant F test, significant T test, and linear regression analysis. The results of research that have been carried out by researchers indicate that there is no significant effect between liquidity on tax aggressiveness and there is a significant negative effect between leverage on tax aggressiveness.